(untitled) (INCH : Journal of Infant and Child Healthcare, 2022)
Nutritional status is a state of the body due to food consumption which can be divided into poor, poor, more and good nutritional status. Mother’s knowledge about nutrition will contribute to the quality of food served Attitude is a factor that affects one’s health as well as the fulfillment of nutrition which can improve the nutritional status of children. The purpose of this research is to study the nutritional picture of mother of children under five about nutrition and nutritional status of children under five. This type of research is a descriptive study, with a cross sectional approach. The population in this study were toddlers in the Work Area of Simpang Tiga Pekanbaru Health Center as many as 54 toddlers. The results of this study indicate more knowledge of maternal nutrition in the sufficient category of 24 people with a prevalence of 42.6% and have a Good Nutrition Status with a prevalence of 76%.